"Ловець у житі" як духовна практика: про рецепцію роману Дж. Д. Селінджера Частина II - Остапенко, Л. М. (My University, 2017)
Стаття присвячена рецепції роману Дж. Д. Селінджера як духовної практики. Авторка бере до уваги християнський аспект твору і пропонує нову інтерпретацію роману "Ловець у житі" з погляду містичної традиції православного християнства - ісихазму.
The article focuses on the J. D. Salinger's novel reception as a spiritual experience. The author investigates of the writing Christian aspect and she proposes a new interpretatbn of the novel 'The Catcher in the Rye", using the means of the Orthodox Mystic Traditbn "hesychasm". The researcher makes a suppositbn about 'The Way of a Pilgrim" and 'The Pilgrim Continues His Way" as the sources of the J. D. Salinger's novel. Thearticb compares spiritual practice of Salinger's heroes. The author proves the importance of the incessant Jesus prayer, applied in hesychasm, in it. The heroes of Salinger overcome spiritual temptations and gain God's grace.
Keywords: "Ловець у житі"; духовна практика; православне християнство; ісихазм; J. D. Salinger; "The Catcher in the Rye"